ESTUDO DAS CARACTERÍSTICAS DE UMA ESTRUTURA TIPO PÓRTICO - Prátzel, Gabriele Cristina; Da Silva, Pâmela Giuli Fleck; Do Nascimento, Angela Andrea Dessbesell Benchimol; Dos Santos, Claudio Da Silva; Valdiero, Antonio Carlos (Salão do Conhecimento, 2014)
Resumo